2022
DOI: 10.1063/5.0079642
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive investigation of vortex-induced vibrations and flow-induced rotation of an elliptic cylinder

Abstract: This work finds its motivation in heat exchanger design and flow control. Flow-induced vibration is studied numerically for combined vortex-induced vibrations and vortex-induced rotations of a horizontally positioned elliptic cylinder. The aspect ratio is taken as 2, and the value of reduced velocities ([Formula: see text]) considered for the present simulation is between 2 and 12. The body can have to and fro motions in a transverse (y) direction, in-line (x) direction as well as in azimuthal ([Formula: see t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Indeed, the motion of each of the sections is linked, as the wind turbine blades were found to vibrate according to structural modes. This, even for relatively more simple configurations such as pivoted cylinders (Shahzer et al, 2022) or cantilever cylinders (Heydari et al, 2022), was found to induce changes in the shedding patterns and the dynamic properties of the coupled system.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the motion of each of the sections is linked, as the wind turbine blades were found to vibrate according to structural modes. This, even for relatively more simple configurations such as pivoted cylinders (Shahzer et al, 2022) or cantilever cylinders (Heydari et al, 2022), was found to induce changes in the shedding patterns and the dynamic properties of the coupled system.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 6 , the vibration model of the tube bundle is simplified into a two-dimensional spring-damp-mass system to improve the calculation efficiency 26 , 27 .
Figure 6 Simplified vibration flexible tube model (m—mass of the tube; k—stiffness of spring; c—damping of the spring-damp-mass system).
…”
Section: Numerical Model For Vibration Of Tube Bundle Under Transvers...mentioning
confidence: 99%